Combined transnasal and transoral endoscopic approach to a transsphenoidal encephalocele in an infant - Tan, S.H.; Mun, K.S.; Chandran, P.A.; Manuel, A.M.; Prepageran, N.; Waran, V.; Ganesan, D. (Springer, 2015)
Purpose This paper reports an unusual case of a transsphenoidal encephalocele and discusses our experience with a minimally invasive management. To the best of our knowledge, we present the first case of a combined endoscopic transnasal and transoral approach to a transsphenoidal encephalocele in an infant.